2019
DOI: 10.1002/tea.21600
|View full text |Cite
|
Sign up to set email alerts
|

Examining tensions in the socioscientific issues classroom: Students' border crossings into a new culture of science

Abstract: In the socioscientific issues (SSI) classroom, students need to cross the border between the subcultures of science (i.e., school science vs. everyday science). Traditional school contexts tend to present science as positivistic knowledge and unshakable truth unaffected by sociocultural factors. In contrast, everyday science, including SSI, is more nuanced, context‐based, socially and culturally embedded. Thus, learning in an SSI classroom requires students to make additional efforts to successfully navigate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 54 publications
1
33
0
1
Order By: Relevance
“…We focus on the construction of different types of arguments because the ability to produce arguments that integrate multiple positions or accounts reflects one's depth of reasoning (Nussbaum & Schraw, 2007). Also, the ability to consider a variety of perspectives is fundamental for decision-making, especially in the case of SSIs, which are complex, open-ended problems that involve controversial and conflicting information (Herman, Zeidler, & Newton, 2018;Lee, Lee, & Zeidler, 2019;Lindahl, Folkesson, & Zeidler, 2019;Zeidler, 2014). Although previous research has shown that there is a relationship between sophisticated epistemic beliefs and argumentation skills, in terms of the number of arguments produced about an issue (Mason & Scirica, 2006;Songer & Linn, 1992;Wu & Tsai, 2011) and the quality of arguments produced (Barzilai & Eshet-Alkalai, 2015;Baytelman, Iordanou, & Constantinou, 2016;Berland et al, 2016;Jiménez-Aleixandre, 2014;McNeill, González-Howard, Katsh-Singer, & Loper, 2017;Ryu & Sandoval, 2012), particularly the ability to construct counterarguments (Iordanou, 2016b;Wu & Tsai, 2011;Zavala & Kuhn, 2017), the relationship between epistemic beliefs and the types of arguments produced (diversity of arguments) has not been investigated yet.…”
Section: The Present Studymentioning
confidence: 99%
“…We focus on the construction of different types of arguments because the ability to produce arguments that integrate multiple positions or accounts reflects one's depth of reasoning (Nussbaum & Schraw, 2007). Also, the ability to consider a variety of perspectives is fundamental for decision-making, especially in the case of SSIs, which are complex, open-ended problems that involve controversial and conflicting information (Herman, Zeidler, & Newton, 2018;Lee, Lee, & Zeidler, 2019;Lindahl, Folkesson, & Zeidler, 2019;Zeidler, 2014). Although previous research has shown that there is a relationship between sophisticated epistemic beliefs and argumentation skills, in terms of the number of arguments produced about an issue (Mason & Scirica, 2006;Songer & Linn, 1992;Wu & Tsai, 2011) and the quality of arguments produced (Barzilai & Eshet-Alkalai, 2015;Baytelman, Iordanou, & Constantinou, 2016;Berland et al, 2016;Jiménez-Aleixandre, 2014;McNeill, González-Howard, Katsh-Singer, & Loper, 2017;Ryu & Sandoval, 2012), particularly the ability to construct counterarguments (Iordanou, 2016b;Wu & Tsai, 2011;Zavala & Kuhn, 2017), the relationship between epistemic beliefs and the types of arguments produced (diversity of arguments) has not been investigated yet.…”
Section: The Present Studymentioning
confidence: 99%
“…Chen et al (2019) found that when science teachers managed uncertainty in an argumentative environment, they tended to reduce or avoid student uncertainty during discussion and treated it as a threat to learning science. Lee et al (2020) explored how South Korean ninth graders discussed a socio‐scientific issue about genetically modified organisms. They found that both teachers and students exhibited a lack of tolerance of uncertainty caused by multiple perspectives and different interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lindahl, Folkesson, and Zeidler (2019) showed that students demand that content be tied to social issues. Other studies, such as Romine, Sadler, and Kinslow (2017) and Herman, Sadler, Zeidler, and Newton (2018) advocate for this approach to teaching, and Lee, Lee, and Zeidler (2019) found that when teachers use social issues as contexts for science education, students need to make additional efforts to apply what they have learned in the classroom to everyday contexts.…”
Section: Discussionmentioning
confidence: 99%